JARINGAN AKTOR DALAM PENGEMBANGAN PARIWISATA DESA WISATA GOGIK KECAMATAN UNGARAN BARAT KABUPATEN SEMARANG - Wijayati, Era; Yuniningsih, Tri; Djumiarti, Titik (Journal of Public Policy and Management Review, 2024)
Tourism development, especially tourism villages in Semarang Regency, is related to the goal of supporting tourism development, equalizing job opportunities, and optimizing economic potential. In fact, Gogik Tourism Village has not yet become a developing tourism village, Pokdarwis and the Gogik Village Government have not carried out their role optimally with a small number of uploads on the Gogik Tourism Village Instagram managed by Pokdarwis and the Gogik Village Government. The existence of the role of actors who have not carried out their roles well shows that the network of actors is not optimal. The purpose of this study is to describe the network of actors formed in the tourism development of Gogik Tourism Village. This research method uses a qualitative descriptive approach, data collection using interviews, observations and documentation. The results of this study show that the network of actors formed in the development of tourism in Gogik Tourism Village is the Helix Quadruple Model consisting of 4 actors, namely the government (Tourism Office, Dispermasdes, Gogik Village Government, PLN, and DLH), academics (UNDIP and UNNES), the community (Pokdarwis, BUMDes, PKK, and Farmer Groups), and the media (Jawa Pos Radar Semarang and Instagram of Gogik Tourism Village). It was found that there were communication and coordination obstacles between government actors and community actors, as well as a lack of influence by community actors in the process of preparing the Gogik Tourism Village tourism development strategy. The suggestion conveyed is to increase the participation of community actors in the planning process by creating a collaborative decision-making process involving community actors and government actors, and communication and coordination obstacles can be faced by holding regular meetings to discuss progress, challenges, and decisions to be taken.